2013
DOI: 10.1039/c3mb25524g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative global phosphoproteomics of human umbilical vein endothelial cells after activation of the Rap signaling pathway

Abstract: The small GTPase Rap1 is required for proper cell-cell junction formation and also plays a key role in mediating cAMP-induced tightening of adherens junctions and subsequent increased barrier function of endothelial cells. To further study how Rap1 controls barrier function, we performed quantitative global phosphoproteomics in human umbilical vein endothelial cells (HUVECs) prior to and after Rap1 activation by the Epac-selective cAMP analog 8-pCPT-2 0 -O-Me-cAMP-AM (007-AM). Tryptic digests were labeled usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Rap1 is an important regulator of cell-cell contacts in a variety of cells, and Rap1 activation can be mediated by several Rap1 GEFs [67], which raises the possibility that other Rap1 GEFs, in addition to Epac and PDZ-GEF1/2, may mediate endothelial barrier stabilization via Rap1. Whereas the mechanisms by which Epac mediates VEC barrier function appear to be diverse, it is noteworthy that a recent comprehensive phosphoproteomics study has shown that the majority of proteins that undergo phosphorylation in response to selective activation of Epac in HUVECs are those involved in facilitating cell-cell junction formation, adhesion and actin reorganization [68]. This further supports the notion that Epac is a central regulator of these processes.…”
Section: Epac-mediated Regulation Of Vec Barrier Functionsupporting
confidence: 58%
“…Rap1 is an important regulator of cell-cell contacts in a variety of cells, and Rap1 activation can be mediated by several Rap1 GEFs [67], which raises the possibility that other Rap1 GEFs, in addition to Epac and PDZ-GEF1/2, may mediate endothelial barrier stabilization via Rap1. Whereas the mechanisms by which Epac mediates VEC barrier function appear to be diverse, it is noteworthy that a recent comprehensive phosphoproteomics study has shown that the majority of proteins that undergo phosphorylation in response to selective activation of Epac in HUVECs are those involved in facilitating cell-cell junction formation, adhesion and actin reorganization [68]. This further supports the notion that Epac is a central regulator of these processes.…”
Section: Epac-mediated Regulation Of Vec Barrier Functionsupporting
confidence: 58%
“…TiO 2 or IMAC, we hypothesise that this is because UPAX separates, rather than specifically enriches, phosphopeptides from non-phosphopeptides. Based on a careful comparison of the number of phosphosites identified using our "all-pX" search strategy with the number of phosphorylation sites identified for the theoretical non-phosphorylatable residue Ala, we show that the commonly applied ptmRS score of 0.75 for "class I" phosphosite localisation (Taus et al, 2011;Meijer et al, 2013;Giansanti et al, 2015;Roitinger et al, 2015;Lombardi et al, 2017) is not acceptable for broad-scale analysis of canonical and non-canonical phosphorylation, since it yields an unacceptably high FLR (Fig 2 and Appendix Tables S5 and S7). To improve confidence in our phosphopeptide datasets, facilitating motif and functional characterisation of the sites and proteins identified, we increased the acceptable site localisation stringency to ptmRS ≥ 0.90, further filtering the data to a ptmRS value ≥ 0.99 for improved confidence when interrogating pX consensus motifs.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Despite the fact that robust workflows have been developed to perform quantitative MS proteomic analysis and extensively used to study phosphorylation dynamics in cell cultures, global phosphoproteomics has only very recently been successfully applied to primary ECs. [18][19][20][21] In this study, we have performed a system-wide and time-resolved characterization of thrombin-induced signaling in primary human blood outgrowth ECs (BOECs). BOECs are ECs derived from human peripheral blood and are a bona fide EC culture model with superior expansion capacity over traditional EC culture models.…”
Section: Introductionmentioning
confidence: 99%